Canonical Poisson structure on T*SE(3) and the Hamiltonian mechanics of solids. Dynamics of a magnetic dipole in the external field - Zub, S. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
We consider a canonical Poisson structure on the cotangent bundle T*SE(3) as a basis for the Hamiltonian mechanics of solids. The Poisson brackets for base dynamic variables are calculated in the different representations. We propose a "mixed" representation so that the forward and rotatory degrees of freedom are described in an inertial reference frame and in the body frame, respectively. The equation of motion is obtained for a magnetic dipole in the external field.